2008
DOI: 10.1124/jpet.107.135905
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin/Orphanin FQ (N/OFQ)-Evoked Bradycardia, Hypotension, and Diuresis Are Absent in N/OFQ Peptide (NOP) Receptor Knockout Mice

Abstract: Intracerebroventricular administration of the opioid-like peptide nociceptin/orphanin FQ (N/OFQ) produces bradycardia, hypotension, and diuresis in mice. We hypothesized that these responses are solely caused by selective activation of central N/OFQ peptide (NOP) receptors. To test this premise, we first examined whether i.c.v. N/OFQ produced dose-dependent diuretic and cardiovascular depressor responses in commercially available C57BL/6 mice. Next, using doses established in these studies, we examined the ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
(46 reference statements)
0
7
1
Order By: Relevance
“…to mice [36]. Further studies likewise reported no differences in MAP between NOP -/- and wild-type mice [8]. However, our findings of tachycardia are in contrast to Burmeister & Kapusta [36].…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…to mice [36]. Further studies likewise reported no differences in MAP between NOP -/- and wild-type mice [8]. However, our findings of tachycardia are in contrast to Burmeister & Kapusta [36].…”
Section: Discussioncontrasting
confidence: 45%
“…N/OFQ also increased aortic blood flow and induced dilation of large blood vessels >200 µm [4,7]. The cardiovascular effects of N/OFQ are absent in mouse knockouts for NOP (NOP -/- ) [8]. Within smaller blood vessels (15 to 40 µm) N/OFQ also induces dilation, along with inflammatory responses such as increased permeability and leukocyte-endothelial interactions within postcapillary venules [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the peripheral actions of PNOC have not been fully described. Outside the brain, OPRL1 has been detected in the rat peripheral ganglia, airways, and intestines; the mice heart, vas deferens, and colon; the guinea pig retina; and in the human airways and mononuclear cells [6][7][8][9][10][11]. As regards the visceral smooth muscles, PNOC has been found to inhibit nonadrenergic-noncholinergic bronchoconstriction in the guinea pig airways via the prejunctional modulation of tachykinin release [12] and to inhibit distal colon motility in the rat [13].…”
Section: Introductionmentioning
confidence: 96%
“…(C) The dose-dependent anti-arrhythmic effects of UFP-101 (n = 6 for each dose); (D) the profile of episodes of VEB in the 60 min of CAO in the experimental groups. △difference (P < 0.01 vs. sham); ▲difference (P < 0.01 vs. CAO); *difference (P < 0.01 vs. UFP7); UFP11, UFP-101 at 10 −11 mol·kg Previous reports indicate that the N/OFQ receptor mediates the cardiovascular effects of N/OFQ (Champion et al, 1997;Giuliani et al, 1997;Dumont and Lemaire, 1998;Burmeister et al, 2008) and UFP-101. UFP-101 can reverse central and peripheral actions of N/OFQ (Calo et al, 2005).…”
Section: Figurementioning
confidence: 96%